2021
DOI: 10.3390/nu13030755
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship between Perceived Meal Colour Variety and Food Intake across Meal Types in a Smartphone-Based Ecological Momentary Assessment

Abstract: Although most people are aware of the health benefits of consuming sufficient amounts of fruit and vegetables, many do not adhere to current dietary recommendations. Recent studies have suggested meal colour variety as an intuitive cue for healthy and enjoyable lunch meal choices. The present study extends this research by testing the “colourful = healthy” association across meal types. Using smartphone-based Ecological Momentary Assessment, 110 participants recorded 2818 eating occasions over a period of eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…An additional record was identified through forward chaining, which resulted in a total of 46 articles being included in this review. Data were extracted from each of the 46 articles and then merged with their respective studies where necessary (seven in total) and reported herein as independent studies ( n = 39) [ 8 , 9 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…An additional record was identified through forward chaining, which resulted in a total of 46 articles being included in this review. Data were extracted from each of the 46 articles and then merged with their respective studies where necessary (seven in total) and reported herein as independent studies ( n = 39) [ 8 , 9 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies were conducted in the United States [ 8 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 33 , 35 , 36 , 40 , 43 , 45 , 50 , 59 , 63 , 64 ], seven in Germany [ 37 , 39 , 41 , 61 , 62 , 65 , 66 , 67 ], six in Austria and Germany [ 49 , 51 , 52 , 56 ], five in Australia [ 38 , 46 , 47 , 48 , 57 , 58 ], two in Austria [ 53 , 54 ] and one each in China [ 60 ], Poland [ 31 , 32 ], Sweden [ 42 ], Taiwan [ 44 ] and the Netherlands [ 9 ]. All studies were observational studies, including 3 cohort studies and 36 cross-sectional studies ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations